The Effect of Transformational Leadership Style on the Performance of Public Sector Civil Servants Within the West Sulawesi Provincial Government - Siti Syahrani Yusuf; Ahmad Yasser Mansyur; St. Hadjar Nurul Istiqamah (Journal of Social Research, 2026)
The performance of civil servants in public organizations remains a critical concern, particularly within the West Sulawesi Provincial Government, where employee productivity is not yet optimal. This study aims to examine the influence of transformational leadership style on civil servant performance. A quantitative approach was applied, involving 277 civil servants selected through proportional random sampling from seven regional apparatus organizations. Data were collected using the **Individual Work Performance Questionnaire (IWPQ)** and the **Multifactor Leadership Questionnaire (MLQ)**. The data were analyzed using simple and multiple linear regression analyses. The findings indicate that transformational leadership has a positive and significant effect on employee performance. Simple regression shows a significant effect with a contribution of 2.2%, while multiple regression indicates that the four leadership dimensions collectively explain 35.3% of the variance in performance. Inspirational motivation emerged as the most dominant dimension influencing performance. Transformational leadership effectively enhances civil servant performance, suggesting that strengthening leadership practices can improve public sector productivity and behavioral outcomes. These findings have implications for leadership development and bureaucratic reform in regional government institutions. Future studies are recommended to include additional variables such as organizational culture, work environment, and compensation systems to improve the explanatory power of the model.